Mengelola Keluhan Digital : Studi tentang Kualitas Komunikasi dan Penanganan Masalah Aplikasi DANA pada Mahasiswa Fakultas Ekonomi Universitas Negeri Medan - Lubis, Adelina; Effendi, Ihsan; Alexander Sabastian Pangaribuan; Maysri Handayani Putri Sinaga (STIE Widya Manggala, 2025)
This study aims to determine the effect of communication quality and problem handling on user complaints of the DANA application, especially for students of the Faculty of Economics, State University of Medan. The background of this study is the increasing user complaints about the DANA application, such as slow customer service response, failed transactions, and lack of clarity in problem solving. This study used a quantitative approach with a survey method, and data were obtained through questionnaires distributed to 100 respondents selected by purposive sampling. The research instrument measured three variables: communication quality (X₁), problem handling (X₂), and user complaints (Y), with a Likert scale of 1-5. The reliability test results show that all variables have Cronbach's Alpha values above 0.8, which means they are highly reliable. The results of multiple linear regression analysis show that communication quality has a positive and significant effect on user complaints (t count = 2.206; sig = 0.03), and problem handling has a significant negative effect (t count = -2.480; sig = 0.015). The simultaneous test (F count = 5.190; sig = 0.007) shows that both variables together have a significant effect on user complaints. This study concludes that improving communication and problem handling can reduce the level of complaints and increase user satisfaction with the DANA application.